Pathophysiology and Reversibility of Prolonged Knee Joint Immobilization: A Comprehensive Temporal Investigation Using an Animal Model - Zhou, Haodong (Université d'Ottawa / University of Ottawa, 2022)
The knee joint is a diarthrodial joint that rotates in the flexion-extension axis to provide individuals mobility. A limitation in the passive range of motion (ROM) is detrimental for function and this limitation is termed a joint contracture. A commonly shared characteristic between conditions that lead to contracture formation is prolonged periods of immobilization. However, the etiology of immobility-induced joint contractures is not well described and requires quantitative data on anatomical structures limiting knee mobility to design new interventions aimed at restoring function. In turn, our research group has developed an experimental animal model to study the temporal pathophysiology of knee immobilization and reversibility through unassisted remobilization. With durations of immobilization ranging from 1 to 32 weeks and remobilization up to 48 weeks, our experimental design provides a comprehensive temporal overview on the various stages of contracture formation: initiation, progression, and severity. A combination of muscles and articular structures are involved in the pathophysiology of knee flexion contractures, but the posterior joint capsule is of particular interest. Through histomorphological analysis, we provided quantitative data on the contribution of the reduced posterior capsule length in the limitation of knee extension and increased joint stiffness. Moreover, elucidation of synoviocyte profiles within the synovium of the capsule provided insights to potential mechanisms of capsule shortening. Our novel measurable outcome of mechanical joint stiffness revealed distinct temporal differences with ROM measurements after joint immobilization and remobilization, suggesting that alterations in the biomechanical properties of articular tissue structures are also contributing to the limitation in function. Malleability of the dynamic reciprocal relationship between trabecular bone loss and accumulation of marrow adipose tissue (predominately through adipocyte hyperplasia) after knee immobilization underscores the sensitivity of the bone marrow microenvironment in response to mechanical stimuli and lack thereof. Remobilization of the knee joint is limited in its capacity to reverse detriments induced by extended periods of joint immobilization. Findings from this work point to the temporal changes detected in different musculoskeletal tissues during knee immobilization and emphasizes the contribution of the joint capsule in limiting joint mobility.
Keywords: Knee; Joint Contracture; Range of Motion; Joint Immobilization; Posterior Joint Capsule; Bone Marrow; Rehabilitation; Biomechanics; Histomorphometry